Tibet a history - Van Schaik, Sam (Yale University Press, 2011)
Presents a comprehensive history of the country, from its beginnings in the seventh century, to its rise as a Buddhist empire in medieval times, to its conquest by China in 1950, and subsequent rule by the Chinese.